2020
DOI: 10.3390/agronomy10111714
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Grain Sorghum and Forage of the Genus Brachiaria in Integrated Agricultural Production Systems

Abstract: Forages of the genus Brachiaria stand out among those used in integrated systems. Little is known about the potential value of new species and cultivars when intercropped with sorghum and planted in the second crop season. The objective of this study was to evaluate the performance (agronomic characteristics) of grain sorghum and the production and nutritional characteristics of forage plants of the genus Brachiaria in an integrated agricultural production system in the second season. The experiment had a rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 53 publications
(67 reference statements)
1
8
1
1
Order By: Relevance
“…According to SANTOS et al ( 2019), sorghum easily adapts to direct competition with other species. Among physiological responses to competition for light and physical space, stem elongation is one of most known (OLIVEIRA et al, 2020). In the present study, sorghum showed 2.7% increased height and 43.7% decreased stem diameter compared to corn.…”
Section: Discussionmentioning
confidence: 45%
“…According to SANTOS et al ( 2019), sorghum easily adapts to direct competition with other species. Among physiological responses to competition for light and physical space, stem elongation is one of most known (OLIVEIRA et al, 2020). In the present study, sorghum showed 2.7% increased height and 43.7% decreased stem diameter compared to corn.…”
Section: Discussionmentioning
confidence: 45%
“…Importantly, with a dry biomass production of approximately 20,000 kg ha -1 of the grain sorghum hybrid BRS 330, grown after soybean, it represents an exciting option for straw production for the notill system, as highlighted by Rossi et al (2013) for the same locality. Furthermore, sorghum biomass produced after soybean becomes an alternative for animal feed in integrated crop-livestock systems in the Cerrado (Oliveira et al, 2020a(Oliveira et al, , 2020bSantos et al, 2020;Sousa Júnior et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The agronomic parameters that were evaluated were the following (Oliveira et al, 2020): grain yield in grams per plant (GY) was determined at harvest, for this, five representative plants from each plot were selected, which were threshed individually, then the grain was weighed and the value was reported as average in grams per plant (g/plant); days to flowering (DF), considering the number of days elapsed from the moment of sowing until the population was in the beginning of anthesis; panicle length (PL), comprises the distance between the base of the panicle to its apex; exertion length (EL), was measured from the flag leaf to the base of the neck of the panicle; plant height (PH), considers the measure from the base of the plant to the tip of the panicle. These variables were evaluated in physiological maturity and the result was expressed in cm.…”
Section: Evaluation Of Agronomic Parametersmentioning
confidence: 99%